Pediatric Fibrinogen PART II—Overview of Indications for Fibrinogen Use in Critically Ill Children - Crighton, Gemma Louise; Huisman, Elise J. (Frontiers in Pediatrics, 2021)
Bleeding is frequently seen in critically ill children and is associated with increased morbidity and mortality. Fibrinogen is an essential coagulation factor for hemostasis and hypofibrinogenemia is an important risk factor for bleeding in pediatric and adult settings. Cryoprecipitate and fibrinogen concentrate are often given to critically ill children to prevent bleeding and improve fibrinogen levels, especially in the setting of surgery, trauma, leukemia, disseminated intravascular coagulopathy and liver failure. The theoretical benefit of fibrinogen supplementation to treat hypofibrinogenemia appears obvious, yet the evidence to support fibrinogen supplementation in children is sparce and clinical indications are poorly defined. In addition, it is unknown what the optimal fibrinogen replacement product is in children and neonates or what the targets of treatment should be. As a result, there is considerable variability in practice. In this article we will review the current pediatric and applicable adult literature with regard to the use of fibrinogen replacement in different pediatric critical care contexts. We will discuss the clinical indications for fibrinogen supplementation in critically ill children and the evidence to support their use. We summarize by highlighting current knowledge gaps and areas for future research.